Settlement-Territorial Identity - Birkner Zoltán; Tivadar Máhr; Nóra Rodek Berkes (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Belonging to groups is an integral part of our lives. We can interpret this to our narrower environment (family, friends, workplace), or in the extended space, to our cities and regions. These bonds only exist as long as the members consider the relationship valuable and important. Binding to a group is called identity. A research was carried out in 2017 in which we interviewed the decision makers of Central European cities about territorial identity. In this study we intend to interpret identity primarily on a territorial basis. Furthermore, we examine the elements of settlement identity, find good practices according to settlement affiliation and present the research results.
Keywords: O35; 330; territorial identity; good practices; community development